ANALISIS PENYELUNDUPAN HUKUM KEPEMILIKAN HAK ATAS TANAH BAGI WARGA NEGARA ASING DENGAN CARA PELANGSUNGAN PERKAWINAN DENGAN WARGA NEGARA INDONESIA - RISTI DWI RAMASARI (PRANATA HUKUM, 2017)
Issues concerning the land can be prevented, at least to reduce the potential to avoid the cause, the problems are legal events, so the causes can be known and recognized by re-looking through existing legal ground view. From the problems in court, the process of settling the case takes a long time, sometimes for many years, it is because of the level of court that must be passed the District Court or Administrative Court, High Court, and Supreme Court.The problem in this paper is how the legal protection of land ownership rights for foreigners with the marriage with the citizens of Indonesia?egal protection of ownership of land rights for foreign nationals with marital sustainability with Indonesian citizens as a means of tenure of land ownership by foreign. By applying the nominee agreement, foreign nationals may control land as possessing land rights as Indonesian citizens. However, this agreement has not been regulated in Indonesia, especially the legal system of agreements set forth in the Civil Code (KUHPdt), so it is categorized into the category of legal smuggling of land ownership rights for foreigners. The legal effort to be taken in solving the problem of legal smuggling of land ownership rights for Foreigners with Marriage Sustainability with Indonesian Citizens is inseparable from the provisions of Article 1320 and Article 1338 of the Civil Code (KUHPdt).